Management of Online Transportation Services at the Gorontalo City Grab Office - Rasid Botuwa; Gobel, Lisda Van; Antu, Yahya (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of this research is to find out the Management of Online Transportation Services at the Gorontalo City Grab Office. This research method is descriptive qualitative. Location: This research was conducted at the Gorontalo City Grab Office. The research results show that Management of Online Transportation Services at the Gorontalo City Grab Office. It can be seen from the results of the interview that the planning limits on the recruitment of new drivers are increasing every day to maintain a balance between drivers and customers. If drivers exceed customers, it will be increasingly difficult for drivers to get orders. It can be seen from the results of interviews that communication between drivers and customers often leads to misunderstandings, such as differences in customer pick-up or delivery locations, which leads to customers canceling orders. It can be seen from the interview results that Grab's supervision is still lacking for customers to maintain driver comfort. When there are individuals who violate the rules, especially customers who often make fictitious orders and cancel orders, this is detrimental to drivers.